Reading To Live : The Evolving Practice of Lectio Divina - Studzinski, Raymond, 1943- (Book collections on Project MUSE., 2009)
Lectio divina, the ancient practice of prayerful reading, is a font whose waters are waiting to quench the thirst of spiritual seekers, both beginners on the spiritual journey and experienced travelers. The art of holy reading transforms lives. Through the practice of lectio individuals and communities discover God's living word addressed to them in their particular now," to enlighten, challenge, encourage, and suggest. Reading to Live traces the practice of lectio divina from its roots in the ascetic movement in the early church and monasticism to its rediscovery in recent times. The benefits lectio brings become clear as Origen, Augustine, Bernard, and many others throughout history testify to its power in their lives. Modern commentators from a variety of disciplines spell out lectio's potential for the world of the twenty-first century. This book invites people of all faiths to embrace the Venerable practice of lectio divina. It provides abundant creative testimonies to its practice and to its life-changing effects. Raymond Studzinski, OSB, a monk of St. Meinrad Archabbey in Indiana, is an associate professor in the School of Theology and Religious Studies at The Catholic University of America, Washington DC, where he teaches courses on religious development and spirituality.